Hesitancy towards COVID-19 vaccination: The role of personality traits, anti-vaccine attitudes and illness perception. - Eric Nanteer-Oteng; Irene A Kretchy; Deborah Odum Nanteer; James-Paul Kretchy; Joseph Osafo (Public Library of Science (PLoS), 2022)
There is an increased need for COVID-19 vaccination since the world is gradually returning to normal. Current evidence supports vaccination activity more towards viral suppression than COVID-19 prevention. This has led to divergent views regarding vaccination which may influence anti-vaccine attitudes and vaccine hesitancy. The study examined the role of personality traits, anti-vaccine attitudes and illness perceptions on vaccine hesitancy. The study was a cross-sectional survey using snowball and convenience sampling to recruit 492 participants via social media platforms. Multivariate analysis of variance and regression analysis were used to test the hypotheses. The study found that some facets of illness perception (identity, concern, emotional representation and treatment control), extraversion, experience with COVID-19 and anti-vaccine attitudes (mistrust, profiteering, worries about unforeseen effects of vaccine) predicted vaccine hesitancy. The outcomes from this study have implications for achieving public health goals and developing strategies for reaching optimal vaccination targets and attaining herd immunity. Health-promoting programs need to be intensified and could include psychosocial perspectives on vaccine hesitancy so that specific target groups can be reached to be vaccinated.